2007
DOI: 10.4137/cmo.s343
|View full text |Cite
|
Sign up to set email alerts
|

Walking outside Improves Mood for Healthy Postmenopausal Women

Abstract: Background: Exercise has been shown to decrease breast cancer risk and slow the progression of breast cancer. Physician recommendations and clinical research data most often are for gym-based exercise programs. However, the importance of exercise location on mood and stress hormones that may infl uence adherence to exercise has not been addressed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
68
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(71 citation statements)
references
References 38 publications
2
68
1
Order By: Relevance
“…However, it is notable that the majority of trials indicating superior effects of outdoor exercise have involved walking (Focht, 2009;Kinnafick & Thøgersen-Ntoumani, 2014;Ryan et al, 2010;Teas, Hurley, Ghumare, & Ogoussan, 2007), while previous trials of running have also found the well-being improvements to be similar in natural and synthetic settings (Kerr et al, 2006;McMurray et al, 1987). It may be that the influence of the environment is strongest with lower-intensity exercise that allows more attention to be paid to surroundings.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is notable that the majority of trials indicating superior effects of outdoor exercise have involved walking (Focht, 2009;Kinnafick & Thøgersen-Ntoumani, 2014;Ryan et al, 2010;Teas, Hurley, Ghumare, & Ogoussan, 2007), while previous trials of running have also found the well-being improvements to be similar in natural and synthetic settings (Kerr et al, 2006;McMurray et al, 1987). It may be that the influence of the environment is strongest with lower-intensity exercise that allows more attention to be paid to surroundings.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, we drew on a study comparing similar short-term effects of an outdoor/indoor exercise bout on a sample size of 24 postmenopausal women. 31 All analyses were conducted using SPSS software version 17.0 (SPSS Inc, Chicago, IL). Statistical significance was set at P e 0.05.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…Participating in physical activity and experiencing nature both play an important role in positively influencing our health and well-being. Short-term walking interventions, particularly in greenspaces, energize and enhance personal well-being and vitality (Peacock et al, 2007; Plante et al, 2007; Teas et al, 2007; Barton et al, 2009; Focht, 2009; Ryan et al, 2010) although walking combined with virtual reality settings depicting natural ecosystems also relaxes and enhances well-being (Plante et al, 2003, 2006). Similarly, running in nature enhances the exercise experience, modifies physiology and mood and increases overall well-being (McMurray et al, 1988; Harte and Eifert, 1995; Kerr et al, 2006; Hug et al, 2008).…”
Section: Development Interaction With Nature and Restorationmentioning
confidence: 99%